2018
DOI: 10.1016/j.bmc.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DK419, a potent inhibitor of Wnt/β-catenin signaling and colorectal cancer growth

Abstract: The Wnt signaling pathway is critical for normal tissue development and is an underlying mechanism of disease when dysregulated. Previously, we reported that the drug Niclosamide inhibits Wnt/β-catenin signaling by decreasing the cytosolic levels of Dishevelled and β-catenin, and inhibits the growth of colon cancers both in vitro and in vivo. Since the discovery of Niclosamide’s anthelmintic activity, a growing body of literature indicates that Niclosamide is a multifunctional drug. In an effort to identify de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Despite the clear rationale for inhibiting the Wnt/β-catenin pathway in colorectal cancer, developing effective strategies to intervene in this pathway clinically has proven challenging (1,3). Through a high-content drug screen, we previously discovered the approved anthelmintic drug niclosamide as an inhibitor of the Wnt pathway (4) and have developed several niclosamide derivatives with improved pharmacological properties to overcome its low bioavailability and poor systemic exposure, including a nanoparticle formulation of a niclosamide conjugate (7,11,25). However, the clinical use of niclosamide and its derivatives to treat systemic diseases such as cancer, requires a more detailed understanding of the mechanism of its drug action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the clear rationale for inhibiting the Wnt/β-catenin pathway in colorectal cancer, developing effective strategies to intervene in this pathway clinically has proven challenging (1,3). Through a high-content drug screen, we previously discovered the approved anthelmintic drug niclosamide as an inhibitor of the Wnt pathway (4) and have developed several niclosamide derivatives with improved pharmacological properties to overcome its low bioavailability and poor systemic exposure, including a nanoparticle formulation of a niclosamide conjugate (7,11,25). However, the clinical use of niclosamide and its derivatives to treat systemic diseases such as cancer, requires a more detailed understanding of the mechanism of its drug action.…”
Section: Discussionmentioning
confidence: 99%
“…We were the first to discover niclosamide, an FDA-approved anthelmintic drug, as a novel inhibitor of Wnt/β-catenin signaling (4). Subsequently, we found that niclosamide and its derivatives have anticancer effects in colorectal cancer cells both in vitro and in vivo, without observable toxicity (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…DK419 is a derivative of niclosamide with multifunctional activity and improved pharmacokinetic properties. It is a promising drug for the treatment of colorectal cancer and Wnt-related diseases [ 256 ]. Inhibition of Wnt secretion by blocking the acidification of an important post-translational modification of palmitoleic provides a useful therapeutic intervention.…”
Section: Drugs and Inhibitorsmentioning
confidence: 99%
“…To the best of our knowledge, there has been a total of 70 drug compounds available in literature with experimentally validated effectiveness for internalizing Frizzled receptor proteins, and thus inhibiting Wnt signaling in human U2OS cells [21], [27]- [29]. Specifically, all these 70 compounds have been classified as active [inactive] compounds if they were able [unable] to induce the internalization of Frizzled receptor proteins, according to the cell imaging data from before and after applying the compound to the cell culture.…”
Section: A Datasetsmentioning
confidence: 99%
“…Some of these diseases (e.g., lung cancer) are associated with altered function/levels of proteins in specific Wnt/-catenin pathways (one type of Wnt signaling pathway), which lead to elevated gene expression that influences cell proliferation and survival [21]. For this reason, inhibition of Wnt/-catenin signaling by small molecule modulators (e.g., Niclosamide) is being considered and developed as a candidate cancer treatment [21], [26]- [29]. For instance, screening assays based on live cell imaging have been used to identify Wnt/-catenin inhibitors [30].…”
Section: Introductionmentioning
confidence: 99%